The effect of flow on the physical properties of polyurethane/carbon nanotubes nanocomposites: Repercussions on their use as electrically conductive Hot‐Melt adhesives. Issue 4 (29th March 2014) - Landa, M.; Fernández, M.; Muñoz, M.E.; Santamaría, A.
Abstract : The properties of multiwall carbon nanotubes (MWCNT)/polyurethane (PUR) nanocomposites after being submitted to flow, i.e., in conditions similar to their application as electrically conductive adhesives (ECA), are investigated. A decrease of the elastic modulus is observed after flow is stopped, compatible with a rearrangement of the MWCNT/PUR network during flow. The implications of the viscoelastic results on probe‐tack data are elucidated and a slightly higher energy of adhesion is observed for sheared samples. Dynamic viscoelastic measurements reveal that crystallization of PUR is fastened with MWCNTs, shortening the solidification process for samples submitted to flow or not. Electrical conductivity results show that the 4 wt% MWCNT/PUR nanocomposite can be submitted to flow and give, on cooling to room temperature, values of the electrical conductivity between 10 −2 and 10 −1 Siemens /m. 2 wt% MWCNT/PUR sample presents a shear induced semiconductor to insulator transition and a temperature‐induced isolator to semiconductor transition. We conclude that MWCNT/PUR nanocomposites are good candidates to develop Hot Melt ECAs, since they display satisfactory viscosity, tack, crystallization (linked to permanent adhesion), and electrical conductivity. POLYM. COMPOS., 36:704–712, 2015. © 2014 Society of Plastics Engineers